2020
DOI: 10.1002/ar.24461
|View full text |Cite
|
Sign up to set email alerts
|

Is the cortical capillary renamed as the transcortical vessel in diaphyseal vascularity?

Abstract: A recent article published in Nature Metabolism, "A network of trans-cortical capillaries as a mainstay for blood circulation in long bones," explained the long bone vascularity. In the mouse model, the authors demonstrated hundreds of transcortical vessels (TCVs) commencing from the bone marrow and traversing the whole cortical thickness. They realized that TCVs were the same as bleeding vessels of periosteal bed observed in the human tibia and femoral epiphysis during surgery. TCVs expressed arterial or veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…The location of the adiponectin -/low FF BMAds aligns with known sites of arteriolar entry and distribution within the femur and tibia (26,27). These cells also expressed Cxcl12, though this was decreased relative to control BMAds.…”
Section: Ectopic Ff Bmads Originate From Adiponectin -/Low Progenitors and Express Low Levels Of Cxcl12supporting
confidence: 60%
“…The location of the adiponectin -/low FF BMAds aligns with known sites of arteriolar entry and distribution within the femur and tibia (26,27). These cells also expressed Cxcl12, though this was decreased relative to control BMAds.…”
Section: Ectopic Ff Bmads Originate From Adiponectin -/Low Progenitors and Express Low Levels Of Cxcl12supporting
confidence: 60%
“…This ectopic BMA population did not rescue circulating adiponectin in the FF mice and had decreased expression of Adipoq, reinforcing the efficacy of the DTA. The location of the FF BMAs aligns with known sites of arteriolar entry and distribution within the femur and tibia (24,25). These cells also expressed Cxcl12, though this was decreased relative to control BMAs.…”
Section: Discussionsupporting
confidence: 64%
“…These periosteal vascular bed-derived TCVs are now recognized as the major cortical blood supply. (Moulopoulos & Koutoulidis, 2015) The channels have been variably labeled as capillaries, vascular lattices, or transosteal channels or vessels of the cortical canal, (Asghar et al, 2020) while Herisson et al (Herisson et al, 2018) and GrĂŒneboom et al(GrĂŒneboom et al, 2019) suggest labeling them at TCVs. Herisson et al (Herisson et al, 2018) reported 21.6 ± 0.9 ÎŒm diameter channels in mice distributed throughout skull cortices in mice, noting similar channels in humans (obtained during decompression surgery) have 5.3-fold larger diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Some porotic alterations may be related to marrow hyperplasia, but another pathophysiologic mechanism deserves consideration. The recent article by GrĂŒneboom et al (GrĂŒneboom et al, 2019) described the presence of hundreds of transcortical capillaries in normal mice postcranial bones and that “diseases that affect bone physiology lead to substantial changes in TCV (transcortical vessel) numbers.” Asghar et al (Asghar et al, 2020) provides a historical review of bone vascularity, noting the first observation of small veins on the shinbone of a cow in 1679 by Antnie van Leeuwenhoek, Clopton Havers' 1,691 recognition of the significance of nutrient arteries penetrating bone, and Albinus' 1754 visualization of blood vessels in bony canals and that there is a combined periosteal and medullary circulation. Brookes (Brookes, 1960) notes communication of cortical capillaries with both the periosteal bed and marrow sinusoids and that centripetal flow occurs at least when medullary artery pressure is compromised.…”
Section: Discussionmentioning
confidence: 99%